1997
DOI: 10.1023/a:1018847626936
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We hypothesized that the inhibitory neurotransmitters nitric oxide (NO) and vasoactive intestinal peptide (VIP) may play a role in the disrupted gastrointestinal motility of endotoxemia. Strain gauge transducers on the stomach and small intestine of dogs determined interdigestive gastrointestinal motility. Tissue levels of NO synthase and VIP and serum levels of nitrite/nitrate (NO(2)-/NO(3)-) and VIP were measured. Following completion of the baseline studies, dogs were given a single dose of E. coli lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…In particular, nitric oxide, vasoactive intestinal peptide, and substance p have been proven to effect gastrointestinal tract motility, in terms of inhibition [2,5]. Through a study carried out on dogs, it has been shown that vasoactive intestinal peptide and nitric oxide cause the deceleration of the gastrointestinal system [6,7]. Additionally, it is a fact that opioids are the potential modulators of the central and peripheral neural system.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, nitric oxide, vasoactive intestinal peptide, and substance p have been proven to effect gastrointestinal tract motility, in terms of inhibition [2,5]. Through a study carried out on dogs, it has been shown that vasoactive intestinal peptide and nitric oxide cause the deceleration of the gastrointestinal system [6,7]. Additionally, it is a fact that opioids are the potential modulators of the central and peripheral neural system.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium transport follows the electrochemical gradient. It is usually absorbed passively in the small intestine and secreted in the colon ( Binder and Sandle , 1991; Guilford and Strombeck , 1996; Cullen et al., 1997; Rolfe et al., 2002). The amplitude of this secretion is determined by the electrochemical force exerted on potassium through the luminal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время накоплено достаточное количество фактов, свидетельствующих о том, что в механизмах нарушения моторики ТК при эндотоксемии принимают участие NO-зависимые процессы: NO -как ключевой фактор в генерации воспалительного ответа и NO -как основной тормозной нейротрансмиттер в кишечнике. Внутривенное введение ЛПС вызывает усиление генерации NO активированными макрофагами в мышечной оболочке кишечника, что приводит к подавлению сократительной активности гладких мышц [16,17].…”
Section: Discussionunclassified